Unlocking organizational productivity through digital marketing: How value proposition strategy shapes success in the service industry - Mawahreh, Mamdouh Abdel Latif Al; Momani, Raed Ahmad; Allahham, Mahmoud; Almagharbeh, Bashar Khaled; Ahmad, Ahmad Y, Bani (International Journal of Innovative Research and Scientific Studies, 2025)
The study explores the impacts of digital marketing initiatives such as online advertising, social media engagement, and customer analytics on productivity enhancement in service organizations and the mediating role of Value Proposition Strategy. Methods: This study, grounded in a comprehensive literature review and experts' insights, collected data from a structured questionnaire administered to managers from diverse service sectors. Descriptive statistics, correlation analysis, and structural equation modeling (SEM) using Smart PLS were used to analyze the relationships among these variables. Findings also show how the process becomes optimized by digital marketing, interpreting that organizational productivity is driven by process optimization and engagement with the customer. Furthermore, the value proposition strategy also has a significant mediating role, highlighting how the unique value offered by companies optimizes the impact of digital marketing efforts. A key insight from the research is using the former to apply two approaches as the key motivation for productivity and sustainability in the long term: building a value proposition and harnessing the power of digital marketing to enhance service management.